Chiral Coupling of Valley Excitons and Light through Photonic Spin–Orbit Interactions. Issue 5 (20th November 2019) - Chen, Peigang; Lo, Tsz Wing; Fan, Yulong; Wang, Shubo; Huang, Haitao; Lei, Dangyuan
Abstract: Spintronics employs the spin of electrons to encode information. Akin to spintronics, valleytronics exploits the valley as pseudospin‐carrying controllable binary information. 2D transition metal dichalcogenides (TMDCs) have asymmetric +K and −K valleys. The valley pseudospins of these materials can be manipulated by selective pumping, giving rise to valley‐dependent circularly polarized photoluminescence. The photonic spin–orbit interactions (SOIs) in nanophotonic systems allow the transformation or coupling of optical spin angular momentum to orbital angular momentum of light. Hybridizing 2D TMDC electronic systems with nanophotonic systems can open up an avenue for merging TMDC valley polarization and photonic SOIs to uncover new mechanisms of on‐chip optical information processing and transport. This review focuses on the fundamentals and implications of TMDC valley polarization, photonic SOI effects, and their chiral coupling in hybrid TMDCs–nanophotonic systems. First, the deterministic valley‐dependent optical properties of TMDCs and recent efforts in achieving large valley polarization contrast are reviewed. Then, various SOI effects in nanophotonic systems and their physical mechanisms are summarized. At the end, recent demonstrations of chiral coupling between TMDC valley excitons and light through spin‐direction locking at hybrid interfaces are highlighted. Abstract : Here, the fundamentals and implications of valley polarization in transition metal dichalcogenides (TMDCs), photonic spin–orbit interaction (SOI), and their chiral coupling in hybrid TMDCs–nanophotonic systems are summarized. The deterministic valley‐dependent optical properties of TMDCs and different types of SOI effects in nanophotonic systems are reviewed. Recent demonstrations of chiral coupling through spin‐direction locking at hybrid interfaces are highlighted.